Effects of High Anxiety Scores on Surgical and Overall Treatment Plan in Patients with Breast Cancer Treated with Neoadjuvant Therapy. (15th October 2019) - LeVasseur, Nathalie; Li, Huaqi; Cheung, Winson; Myers, Paula; Mckevitt, Elaine; Warburton, Rebecca; Willemsma, Kaylie‐Anne; Tan, Adam Deruchie; Chia, Stephen; Simmons, Christine
Abstract: Background: Patients with newly diagnosed breast cancer and high levels of anxiety often pursue more aggressive surgical interventions. The neoadjuvant treatment (NAT) setting could provide a window of opportunity to address patients' anxiety. However, the impact of anxiety on surgical decisions in the setting of NAT for breast cancer has not been previously studied. Materials and Methods: A prospective database of patients with breast cancer treated with NAT at BC Cancer was used to identify patients treated with NAT and subsequent surgical resection. Patients with bilateral breast cancer or BRCA mutations or those referred to the hereditary cancer program were excluded. An anxiety score of 0–3 was assigned based on responses to the Edmonton Symptom Assessment System and Psychosocial Screen for Cancer. Clinicopathological information and treatment data were retrieved and cross‐referenced between the low‐anxiety (scores 0–1) and high‐anxiety (scores 2–3) cohorts. Results: From 2012 to 2016, 203 patients met eligibility criteria. Of these, 93 patients (45.8%) had low anxiety and 110 patients (54.2%) had high anxiety. Overall, 161 patients (79.3%) had locally advanced cancers; no differences in stage, grade, or biomarkers were found between the low‐ and high‐anxiety cohorts. Patients with high self‐reported anxiety at initial consultation were younger (mean 56 years vs. 60 years; p = .011) and more likely to undergo mastectomy for breast‐conserving surgery–eligible disease and bilateral mastectomy for unilateral disease compared with those with low anxiety (37.3% vs. 18.3%; likelihood ratio 9.15; p = .002). No significant differences in treatment timelines were identified between the two cohorts. Conclusion: Patients with high anxiety at initial consultation were nine times more likely to undergo aggressive surgery compared with patients with low anxiety. These findings underscore the need for early identification of patients who may benefit from tailored supportive and educational services to address sources of anxiety and knowledge gaps. Abstract : This article reviews the effect of patient anxiety on decisions related to surgical treatment of early stage breast cancer and the use of self‐reported anxiety as a clinical tool to tailor educational and supportive resources.